Single-Cell Transcriptomic Analysis Unveils Key Regulators and Signaling Pathways in Lung Adenocarcinoma Progression - Jialu Ma; Caleb McQuay; John Talburt; Amit K. Tiwari; Mary Qu Yang (Biomedicines, 2025)
Background: Lung adenocarcinoma (LUAD) remains a leading cause of cancer-related mortality despite advances in treatments, necessitating more effective therapeutic strategies. Single-cell RNA sequencing (scRNA-seq) technology has revolutionized our ability to dissect the cellular complexity of cancers, which is often obscured in conventional bulk transcriptomic experiments. Methods: In this study, we performed an integrative analysis of scRNA-seq data from multiple LUAD patient cohorts to investigate cell-type-specific transcriptomic changes across disease stages. Clustering, lineage trajectory analysis, and transcriptional regulatory network reconstruction were employed to identify stage-specific gene markers and their upstream regulators. Additionally, we constructed intercellular communication networks to evaluate signaling changes within the tumor microenvironment (TME) during LUAD progression. Results: Our analysis revealed that epithelial cells from stage IV tumors exhibited a distinct transcriptional profile compared to earlier stages, a separation not observed in immune or stromal cell populations. We identified a panel of gene markers that differentiated epithelial cells across disease stages and effectively stratified patients into subgroups with distinct survival outcomes and TME compositions. Regulatory network analysis uncovered key transcription factors, including ATF3, ATF4, HSF1, KLF4, and NFIC, as potential upstream regulators of these stage-specific genes. Moreover, cell–cell communication analysis revealed a significant increase in signaling originating from epithelial cells and a concomitant decrease in immune-derived signals in late-stage LUAD. We identified several signaling pathways enriched in stage-specific crosstalk, including Wnt, PTN, and PDGF pathways, which may play critical roles in LUAD progression. Conclusions: This study provides a comprehensive single-cell resolution map of LUAD progression, highlighting epithelial-driven regulatory programs and dynamic intercellular communication within the TME. Our findings uncover novel molecular markers and regulatory mechanisms with potential prognostic and therapeutic value for more precise treatment.